Inhibition of Neurosphere Formation in Neural Stem/Progenitor Cells by Acrylamide. Issue 5 (May 2015) - Chen, Jong-Hang; Lee, Don-Ching; Chen, Mei-Shu; Ko, Ying-Chin; Chiu, Ing-Ming
Previous studies showed that transplantation of cultured neural stem/progenitor cells (NSPCs) could improve functional recovery for various neurological diseases. This study aims to develop a stem cell-based model for predictive toxicology of development in the neurological system after acrylamide exposure. Treatment of mouse (KT98/F1B-GFP) and human (U-1240 MG/F1B-GFP) NSPCs with 0.5 mM acrylamide resulted in the inhibition of neurosphere formation (definition of self-renewal ability in NSPCs), but not inhibition of cell proliferation. Apoptosis and differentiation of KT98 (a precursor of KT98/F1B-GFP) and KT98/F1B-GFP are not observed in acrylamide-treated neurospheres. Analysis of secondary neurosphere formation and differentiation of neurons and glia illustrated that acrylamide-treated KT98 and KT98/F1B-GFP neurospheres retain the NSPC properties, such as self-renewal and differentiation capacity. Correlation of acrylamide-inhibited neurosphere formation with cell-cell adhesion was observed in mouse NSPCs by live cell image analysis and the presence of acrylamide. Protein expression levels of cell adhesion molecules [neural cell adhesion molecule (NCAM) and N-cadherin] and extracellular signal-regulated kinases (ERK) in acrylamide-treated KT98/F1B-GFP and U-1240 MG/F1B-GFP neurospheres demonstrated that NCAM decreased and phospho-ERK (pERK) increased, whereas expression of N-cadherin remained unchanged. Analysis of AKT (protein kinase B, PKB)/β-catenin pathway showed decrease in phospho-AKT (p-AKT) and cyclin D1 expression in acrylamide-treated neurospheres of KT98/F1B-GFP. Furthermore, PD98059, an ERK phosphorylation inhibitor, attenuated acrylamide-induced ERK phosphorylation, indicating that pERK contributed to the cell proliferation, but not in neurosphere formation in mouse NSPCs. Coimmunoprecipitation results of KT98/F1B-GFP cell lysates showed that the complex of NCAM and fibroblast growth factor receptor 1 (FGFR1) is present in the neurosphere, and the amount of this complex decreases after acrylamide treatment. Our results reveal that acrylamide inhibits neurosphere formation through the disruption of the neurosphere architecture in NSPCs. The downregulation of cell-cell adhesion resulted from decreasing the levels of NCAM as well as the formation of NCAM/ FGFR complex.